Cracking the fault line in stock markets: The case of bonus issue announcements - Murat Isiker; Oktay Tas (Journal of Capital Markets Studies (JCMS), 2021)
Purpose - The paper aims to measure the magnitude of the event-induced return anomaly around bonus issue announcement days in Turkey for recent years. Also, by describing the information content of these announcements with the current data, the study tries to find out the factors that cause return anomaly in Borsa Istanbul when firm boards release the bonus issue decision. Design/methodology/approach - The paper conducts event study methodology for detecting market anomaly around bonus issue announcements. For the pairwise comparison purpose, t-test and one-way ANOVA methods are applied to examine if abnormal returns vary according to the information content of the announcements. Findings - Announcement returns for bonus issues from internal resources outperform the issues that are distributed from last year's net income as bonus shares. Findings indicate different return behaviour among internal resources sub-groups. Findings also suggest that investors in Turkey welcome larger-sized issues, while cumulated returns for the initial offers significantly differ from the latter issues. Research limitations/implications - Findings are limited to the Turkish equity market. Also, the Public Disclosure Platform of Turkey, which is the main data source of the study, does not provide bonus issue announcements before 2010. Therefore, the previous year's data cannot be included in the analysis. Originality/value - This paper is novel in terms of considering the main resources of the bonus issue in detail to measure the announcement's impact on stock returns.
Keywords: 330; Bonus issue; Announcement effect; Stock dividend; Market sentiment; Borsa Istanbul; Event study